ORGANIZATION OF WORK OF THE SCHOOL MEDIA SERVICE IN MODERN CONDITIONS: EXPERIENCE OF INNOVATIVE WORK - Tatyana Ivanovna Miticheva (Science and Innovation Center Publishing House, 2019)
The author of the article presents the experience of teachers and student volunteers of the Arzamas branch of the NNGU with students of a secondary school in organizing and scientifically and methodically supporting innovative work in an educational institution in the direction of “Developing a model of the school mediation service as a condition for creating a safe and effective educational environment in the framework of implementation and implementation of the GEF”.